Cultural Genocide - Davidson, Lawrence (Rutgers University Press, 2012)
Most scholars of genocide focus on mass murder. Lawrence Davidson, by contrast, explores the murder of culture. He suggests that when people have limited knowledge of the culture outside of their own group, they are unable to accurately assess the alleged threat of others around them. Throughout history, dominant populations have often dealt with these fears through mass murder. However, the shock of the Holocaust now deters today’s great powers from the practice of physical genocide. Majority populations, cognizant of outside pressure and knowing that they should not resort to mass murder, have turned instead to cultural genocide as a "second best" politically determined substitute for physical genocide. In Cultural Genocide, this theory is applied to events in four settings, two events that preceded the Holocaust and two events that followed it: the destruction of American Indians by uninformed settlers who viewed these natives as inferior and were more intent on removing them from the frontier than annihilating them; the attack on the culture of Eastern European Jews living within Russian-controlled areas before the Holocaust; the Israeli attack on Palestinian culture; and the absorption of Tibet by the People’s Republic of China. In conclusion, Davidson examines the mechanisms that may be used to combat today’s cultural genocide as well as the contemporary social and political forces at work that must be overcome in the process
Description based on online resource; title from PDF title page (publisher's Web site, viewed 05. Mai 2020)
Keywords: Geschichte 1800-2010; POLITICAL SCIENCE / General; Assimilation (Sociology); Ethnic conflict; Indians, Treatment of -- North America -- History; Jews -- Russia -- Social conditions -- 19th century; Persecution -- Social aspects; Unterdrückung; Zwangsassimilation; Minderheitenfrage; Verfolgung